SOVEREIGN DEBT RESTRUCTURINGS: PREEMPTIVE OR POST‐DEFAULT. Issue 1 (22nd January 2016) - Asonuma, Tamon; Trebesch, Christoph
Abstract: Sovereign debt restructurings can be implemented preemptively—prior to a payment default. We code a comprehensive new data set and find that preemptive restructurings (i) are frequent (38% of all deals 1978–2010), (ii) have lower haircuts, (iii) are quicker to negotiate, and (iv) see lower output losses. To rationalize these stylized facts, we build a quantitative sovereign debt model that incorporates preemptive and post‐default renegotiations. The model improves the fit with the data and explains the sovereign's optimal choice: preemptive restructurings occur when default risk is high ex ante, while defaults occur after unexpected bad shocks. Empirical evidence supports these predictions.